Progress report from the Committee for Foreign Correspondence - Federation of American Scientists (1946)
Newsletter from the Committee for Foreign Correspondence of the Federation of American Scientists containing a progress report summarizing the current work of the committee. The primary aim is to "promote an interchange of information and ideas which might help the peoples of all nations to realize the necessity for international atomic energy control and to understand the problems which must be faced in establishing this control."
Keywords: Federation of American Scientists; Nuclear energy